The Role of the Spotify Wrapped Digital Campaign on Spotify Brand Advocacy on Social Media Instagram, Twitter (X), and Tiktok - Ismi Alivia Wulandari; Muria Putriana; Wina Puspita Sari; Asep Soegiarto; Menati Fajar Rizki (Journal of Research in Social Science and Humanities, 2024)
This research aims to determine the contribution of the Spotify Wrapped digital campaign to Spotify brand advocacy on social media (Instagram, Twitter (X), and Tiktok) and determine the participation of Spotify users in become an active brand advocates through the Spotify Wrapped digital campaign. The hypothesis of this research is that there is a positive and significant relationship between user participation in the Spotify Wrapped digital campaign and the level of Spotify brand advocacy on social media (Instagram, Twitter (X), and Tiktok). This research method is descriptive quantitative. The population is 574 million and the sample is 100 which is calculated using the Slovin formula. The sampling technique in this research used a simple random sampling technique. The results of this study show that the Pearson correlation test value is 0.822 with a significance of 0.00. This value can be interpreted that the Spotify Wrapped digital campaign has a positive relationship with Spotify's brand advocacy on social media (Instagram, Twitter (X), and Tiktok). From the simple linear regression analysis, a value of 0.00 is obtained, H1 is accepted, namely that there is a positive and significant relationship between user participation in the Spotify Wrapped digital campaign and the level of Spotify brand advocacy on social media (Instagram, Twitter (X), and Tiktok). Based on these results, the more users are involved in the Spotify Wrapped digital campaign, the higher the level of support and promotion of the Spotify brand on social media platforms (Instagram, X, TikTok), and the greater the possibility of them becoming active brand advocates for Spotify.Keywords: Digital Campaign, Brand Advocacy, Spotify Wrapped, Social Media